2008
DOI: 10.1111/j.1567-1364.2008.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene, ecl1+, extends the chronological lifespan in fission yeast

Abstract: We have identified a novel gene from Schizosaccharomyces pombe that we have named ecl1(+) (extender of the chronological lifespan). When ecl1(+) is provided on a high-copy number plasmid, it extends the viability of both the Deltasty1 MAP kinase mutant and the wild-type cells after entry into the stationary phase. ecl1(+) encodes an 80-amino acid polypeptide that had not been annotated in the current database. The ecl1(+)-mRNA increases transiently when the growth phase is changed from the log phase to the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 24 publications
4
76
1
Order By: Relevance
“…6,7) When each of these genes was overexpressed, the cell survival rate in the stationary phase was higher than that of the controls. We also identified the ECL1 (YGR146c) gene in S. cerevisiae as a functional homolog of the Ecl1 family genes in S. pombe.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…6,7) When each of these genes was overexpressed, the cell survival rate in the stationary phase was higher than that of the controls. We also identified the ECL1 (YGR146c) gene in S. cerevisiae as a functional homolog of the Ecl1 family genes in S. pombe.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we reported that overexpression of Ecl1 causes physiological changes equivalent to the changes caused by CR. 6) Therefore the chronological lifespan of Áphp2 mutant may be extended by mimicking CR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations